New methods for offenders - Molony, Thomas F., Sir (Statistical and Social Inquiry Society of Ireland, 1940)
When the Society did me the honour of electing me President 20 years ago I chose as the subject of my address "The Prevention and Punishment of Crime." I pointed out that the four great methods of preventing crime were (a) to provide the worker with a decent and comfortable home, (6) to encourage temperance, (c) to adopt means for securing regular work, and (d) to provide reasonable opportunities for recreation. I also suggested certain amendments in the law of criminal procedure which I hoped might lead to happy results. While I have already in a Paper read before the Society, dealt with the principles of Probation, the importance of the subject has grown in each succeeding year.
Read on Tuesday, 12th March, 1940
Keywords: Penal system; Offenders; 314.15